Hubungan antara Kekuatan Otot Tungkai dengan Kemampuan Smash pada Pemain Sepak Takraw - Larobi; Agus Kurniadi (Qalam : Jurnal Ilmu Kependidikan, 2024)
AbstractThis study aims to determine the relationship between leg muscle strength and smashing ability in sepak takraw players. The method used was quantitative research with a correlational approach. The subjects were 20 Physical Education students from the University of Muhammadiyah Sorong, selected purposively. Leg muscle strength data were obtained through a vertical jump test, while smashing ability was measured through technical skill assessments by three judges. Data were analyzed using the Pearson Product Moment correlation test. The results showed a significant relationship between leg muscle strength and smashing ability. This means that the greater the leg muscle strength, the better the player's smashing ability. This finding demonstrates the importance of leg strength training in improving sepak takraw smashing performance. Keywords: leg muscle strength, smashing ability, sepak takraw